2023
DOI: 10.1371/journal.pone.0282864
|View full text |Cite
|
Sign up to set email alerts
|

Ratio of extracellular water to intracellular water and simplified creatinine index as predictors of all-cause mortality for patients receiving hemodialysis

Abstract: The bioelectrical impedance analysis-measured ratio of extracellular water (ECW) to intracellular water (ICW) reflects fluid volume and malnutrition. It may be an indicator of protein-energy wasting and muscle wasting in hemodialysis patients. We examined the association between the ECW/ICW ratio and simplified creatinine index, which is a new surrogate marker of protein-energy wasting and muscle wasting, and whether their combination can accurately predict mortality. A total of 224 patients undergoing hemodia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…Blood samples were obtained with the patients in supine position before and after HD at the beginning of the week. Bioelectrical impedance analysis (BIA) was performed in the supine position approximately 30 min after the HD session, when the DW set by the ultrafiltration rate was reached; intracellular water (ICW), extracellular water (ECW) and total body water (TBW), body fat content, skeletal muscle mass, protein content, bone mineral content, basal metabolism and skeletal muscle mass index (SMI) were measured with a body composition meter with multiple frequencies (1 kHz–1 MHz) using the ankle and wrist method [ 11 , 12 ]. The InBody S10 (Biospace Co., Ltd., Seoul, Republic of Korea) was used for measurements.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Blood samples were obtained with the patients in supine position before and after HD at the beginning of the week. Bioelectrical impedance analysis (BIA) was performed in the supine position approximately 30 min after the HD session, when the DW set by the ultrafiltration rate was reached; intracellular water (ICW), extracellular water (ECW) and total body water (TBW), body fat content, skeletal muscle mass, protein content, bone mineral content, basal metabolism and skeletal muscle mass index (SMI) were measured with a body composition meter with multiple frequencies (1 kHz–1 MHz) using the ankle and wrist method [ 11 , 12 ]. The InBody S10 (Biospace Co., Ltd., Seoul, Republic of Korea) was used for measurements.…”
Section: Methodsmentioning
confidence: 99%
“…were measured with a body composition meter with multiple frequencies (1 kHz-1 MHz) using the ankle and wrist method [11,12]. The InBody S10 (Biospace Co., Ltd., Seoul, Republic of Korea) was used for measurements.…”
Section: Study Design and Collection Of Medical Datamentioning
confidence: 99%
See 1 more Smart Citation
“…2127 Previous studies have shown direct correlation between ICW and serum creatinine concentration. 2831…”
Section: Methodsmentioning
confidence: 99%
“…Recently, there has been growing interest in using the ratio of ECW to ICW (ECW/ICW) as a composite index of fluid overload and malnutrition. Yajima et al showed that the ECW/ICW (when measured by MF-BIA) was negatively associated with a simplified creatinine index (a surrogate for muscle mass) in 224 prevalent HD patients [ 87 ]. Moreover, both ECW/ICW (≥0.57) and s simplified creatinine index (<20.4 g/kg/day) were independent predictors of all-cause mortality, and this is after the adjustment of demographics, comorbidities, and albumin levels.…”
Section: Association Of Bioimpedance-derived Nutritional Parameters A...mentioning
confidence: 99%